Pengaruh Employee Engagement, Kompensasi dan Job Insecurity Terhadap Turnover Intention: Study pada Driver PT. Surya Nusa Berkat Abadi - Muhammad Agung Frananta; Antin Rakhmawati; M. Sulhan (MES Bogor, 2025)
This study aims to analyze the effect of employee engagement, compensation, and job insecurity on turnover intention of drivers of PT. Surya Nusa Berkat Abadi. Turnover intention is a crucial issue in this company, especially because high turnover has a negative impact on company operations, increases recruitment costs, and training. This study uses a quantitative method with an explanatory research type. Data were collected through a survey involving all drivers of PT. Surya Nusa Berkat Abadi as respondents. The results of the study indicate that employee engagement, compensation, and job insecurity significantly affect turnover intention. Employee engagement and compensation have a negative effect on turnover intention, which means that increasing employee engagement and providing appropriate compensation can reduce employee intentions to leave the company. Conversely, job insecurity has a positive effect on turnover intention, which indicates that job insecurity increases employee intentions to leave the company. Simultaneously, these three variables significantly affect turnover intention. This study provides practical recommendations for companies to improve employee engagement and provide adequate compensation to reduce turnover intention, as well as better manage job insecurity to maintain workforce stability. The results of this study also contribute to the development of human resource management literature, especially in the context of the transportation industry in Indonesia.